Identification of the cause of the stem neck fracture in the hip joint endoprosthesis - Ryniewicz, Anna Maria; Bojko, Łukasz; Pałka, Paweł; Rynkiewicz, Andrzej; Ryniewicz, Wojciech (Zielona Góra: Uniwersytet Zielonogórski)
Endoprosthesis stem fractures are among the rarest complications that occur after hip joint arthroplasty. The aim of this paper is to evaluate the causes of the fractures of the Aura II stem neck, which is an element of an endoprosthesis implanted in a patient. In order to achieve it, a radiogram was evaluated, the FEM analysis was carried out for the hip joint replaced using the Aura II prosthesis and scanning tests as well as a chemical analysis were performed for the focus of fatigue.
Keywords: prosthetic arthroplasty; stem construction; fatigue fracture; Finite Element Method (FEM); SEM